KOMPOSISI DAN LUAS RELUNG MAKANAN IKAN PALUNG (Hampala macrolepidota C.V.1823) DI WADUK PB. SOEDIRMAN BANJARNEGARA, JAWA TENGAH - Elsa Melisa; Asrul Sahri Siregar; Siti Rukayah (UNIVERSITAS PGRI MADIUN, 2021)
This study aims to determine the composition and value of the natural feed niche of trough fish caught from the waters of the PB Reservoir. Sudirman. The research method used is a survey method with a sampling technique using purposive random sampling. The research location was divided into three stations, namely I (Karang Kemiri), II (Wanadadi), and III (Karang Jambe). Sampling was carried out three times (19 February, 07 March, and 2 August 2020). Data were analyzed descriptively comparatively. The results showed that the composition of the trough fish diet was dominated by Chlorophyta and plant debris. Based on the selectivity index and the most significant part of trough fish, including omnivorous fish. Large trough fish have a high food niche area. Small, medium and large trough fish have stiff competition for food in the waters